Avian orthoavulavirus 1 (Newcastle Disease virus) antibodies in five penguin species, Antarctic peninsula and Southern Patagonia. Issue 6 (9th March 2021) - Ariyama, Naomi; Tapia, Rodrigo; Godoy, Claudia; Agüero, Belén; Valdés, Valentina; Berrios, Felipe; García Borboroglu, Pablo; Pütz, Klemens; Alegria, Raul; Barriga, Gonzalo P.; Medina, Rafael; Neira, Víctor
Abstract: Avian orthoavulavirus 1 (AOaV‐1) causes Newcastle disease, one of the most important and contagious infections in poultry, where migratory birds can play a key role as a reservoir. Seven hundred and seven serum samples were collected from five penguin species (King, Magellanic, Gentoo, Chinstrap and Adelie penguins) in the Antarctic and Sub‐Antarctic zones. Using a competitive ELISA to detect antibodies against AOaV‐1, we identified positive individuals in all penguin species. The Magellanic penguin showed the highest seropositivity rate (30.3%), suggesting it could be a natural reservoir of this virus. At the Antarctic zones, Chinstrap penguin showed the highest occurrence (7.5%). Interesting, positive sera was only obtained in Sub‐Antarctic and Northern zones at the Antarctic peninsula, no seroreactivity was observed in Southern locations. Further studies are needed to establish the role of these penguin species in the epidemiology of the AOaV‐1 and determine the effects of this virus in these populations.